Constitutive and functional expression of YB-1 in microglial cells. (20th August 2015) - Keilhoff, G.; Titze, M.; Esser, T.; Langnaese, K.; Ebmeyer, U.
Highlights: YB-1 mRNA is constitutively expressed and functionally translated in microglia/BV-2 cells. YB-1 protein increases as a result of OGD, OGD-relevant mediators and phagocytosis-inducing factors. LPS is a less effective stimulus of YB-1 expression in BV-2 cells. YB-1 protein levels were primarily regulated by proteasomal degradation and less so by eIF4E activation (phosphorylation). YB-1 up-regulation was not accompanied by its translocation from the cytoplasm to the nucleus. Abstract: Y-box-binding protein (YB-1) is a member of the cold-shock protein family and participates in a wide variety of DNA/RNA-dependent cellular processes including DNA repair, transcription, mRNA splicing, packaging, and translation. At the cellular level, YB-1 is involved in cell proliferation and differentiation, stress responses, and malignant cell transformation. A general role for YB-1 during inflammation has also been well described; however, there are minimal data concerning YB-1 expression in microglia, which are the immune cells of the brain. Therefore, we studied the expression of YB-1 in a clinically relevant global ischemia model for neurological injury following cardiac arrest. This model is characterized by massive neurodegeneration of the hippocampal CA1 region and the subsequent long-lasting activation of microglia. In addition, we studied YB-1 expression in BV-2 cells, which are an accepted microglia culture model. BV-2 cells were stressed by oxygen/glucose deprivation (OGD), OGD-relevant mediators, lipopolysaccharide (LPS), and phagocytosis-inducing cell debris and nanoparticles. Using quantitative polymerase chain reaction (PCR), we show constitutive expression of YB-1 transcripts in unstressed BV-2 cells. The functional upregulation of the YB-1 protein was demonstrated in microglia in vivo and in BV-2 cells in vitro . All stressors except for LPS were potent enhancers of the level of YB-1 protein, which appears to be regulated primarily by proteasomal degradation and, to a lesser extent, by the activation (phosphorylation) of the translation initiation factor eIF4E. The proteasome of BV-2 cells is impaired by OGD, which results in decreased protein degradation and therefore increased levels of YB-1 protein. LPS induces proteasome activity, which enables the level of YB-1 protein to remain at control levels despite enhanced protein ubiquitination. The proteasome inhibitor MG-132 was able to increase YB-1 protein levels in control and LPS-treated cultures. YB-1 upregulation was not accompanied by its translocation from the cytoplasm to the nucleus. YB-1 induction appeared to be related to microglial proliferation because it was partially co-regulated with Ki67. In addition, YB-1 protein levels correlated with microglia phagocytic activity because its upregulation could also be induced by inert NPs.